A Conceptual Model of Cultural Distance, MNC Subsidiary Roles, and Knowledge Transfer in China-based Subsidiaries - Qin, Cindy; Ramburuth, Prem; Wang, Yue (Organizations and Markets in Emerging Economies, 2011)
This conceptual paper seeks to review the literature on international strategic management, examine the trilateral interactive relations among national culture, subsidiary strategic context and knowledge transfer between China-based subsidiaries and their headquarters. Based on the Resource-Based View (RBV), cross-cultural management theories and other studies of international strategic management, we propose a conceptual model for understanding the interaction between cultural distance and subsidiary strategic context in the knowledge transfer process within MNCs, and ultimately the impact on the performance of subsidiaries. Drawing foundational support from this new model, we explore implications for future research.